Carpal tunnel syndrome in acromegaly: a nationwide study. Issue 2 (February 2021) - Vouzouneraki, Konstantina; Esposito, Daniela; Mukka, Sebastian; Granfeldt, Daniel; Ragnarsson, Oskar; Dahlqvist, Per; Olsson, Daniel S
Abstract : Objective: Carpal tunnel syndrome (CTS) is common in patients with acromegaly, with a reported prevalence of 19–64%. We studied CTS in a large national cohort of patients with acromegaly and the temporal relationship between the two diagnoses. Design: Retrospective, nationwide, cohort study including patients diagnosed with acromegaly in Sweden, 2005–2017, identified in the Swedish Healthcare Registries. Methods: CTS (diagnosis and surgery in specialised healthcare) was analysed from 8.5 years before the diagnosis of acromegaly until death or end of the study. Standardised incidence ratios (SIRs) with 95% CIs were calculated for CTS with the Swedish population as reference. Results: The analysis included 556 patients with acromegaly (50% women) diagnosed at mean (s.d .) age 50.1 (15.0) years. During the study period, 48 patients were diagnosed with CTS and 41 patients underwent at least one CTS surgery. In the latter group, 35 (85%) were operated for CTS before the acromegaly diagnosis; mean interval (range) 2.2 (0.3–8.5) years and the SIR for having CTS surgery before the diagnosis of acromegaly was 6.6 (4.8–8.9). Women with acromegaly had a higher risk for CTS than men (hazard ratio: 2.5, 95% CI: 1.3–4.7). Conclusions: Patients with acromegaly had a 6-fold higher incidence for CTS surgery before the diagnosis of acromegaly compared with the general population. The majority of patients with both diagnoses were diagnosed with CTS prior to acromegaly. Increased awareness of signs of acromegaly in patients with CTS might help to shorten the diagnostic delay in acromegaly, especially in women.